Image Quality Differences In CT Scan Thorax By Using Slice Thickness Variation - Samsun Samsun; Legia Prananto; Novita Wulandari (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
The picture quality get from CT Scan of Thorax which required optimal parameter selection that’s right, one of them the selection of slice thickness. The method taken from theses that have been publish in the year 2013. The results of the research show the percentage of the value of the average spatial resolution of 2.5 mm slice thickness is (33.3%), noise (17.8%), artefact (1%). On the thickness of the slices 5 mm spatial resolution is (17%), noise (8.9%), artefacts (0%). On the thickness of slices of 7.5 mm spatial resolution is (8.9%), noise (11.1%), artefacts (53.3%). While the thickness of the slices the spatial resolution is 10 mm (8.9%), noise (22.2%), artefacts (68.9%). Based on the research results obtained the conclusion that thickness 2.5 mm slices on Thorax CT-Scan images produce better picture quality than with the thickness of the slices 5 mm, 7.5 mm, 10 mm, because the spatial resolution is more clear so as to reduce noise and artifacts.